Kerala's Puḷḷuvas and Pāmpum Tuḷḷal : An Ethnography of Ritual Practice - Neff, Deborah L. (Brill | Manohar Publishers & Distributors, 2024)
Kerala's Puḷḷuvas and Pāmpum Tuḷḷal is a story about the lives of Kerala's Puḷḷuva ritual specialists and their days-long ritual performance, pāmpum tuḷḷal, or the "jumping dance" of the serpent deities (nāgam or pāmpu). The ritual is commissioned by members of Kerala's landed communities to bring health and prosperity to their extended families. Belonging to an ancient South Indian tradition, the ritual is orchestrated by Puḷḷuva ritual specialists, who hold the sole hereditary right to perform it. This book is the first in Kerala to approach this ritual tradition from the viewpoints and agency of its Dalit (formerly known as 'untouchable') ritual specialists-men and women, and to examine Puḷḷuva ritual practice in the context of rapid and extensive social change. The study sheds important light upon Puḷḷuva rituals, lives, and livelihoods, within the broader contexts of changing class, caste, and kinship relations; land tenure and ritual patronage; labour migration; and the decline of Nāyar matrilineality and old landed families. These wide-ranging social trends, indexed and acted out in ritual, are the backdrop for understanding Puḷḷuva ritual practice from the 1980s, and in terms of history, point to multiple structures and hierarchies of practice and meaning. The combination of the focused study of ritual performance and traditional ethnography allows readers to witness the ritual practices and lives of members of a small, real-world community rendered virtually absent from the historical record. It's extraordinary to hear from Puḷḷuvas in their own words and to witness their dedication to their sacred profession, at a time when the world they knew was rapidly falling apart. But thirty-plus years later, the story-at least for now, has a happy ending; both Puḷḷuvas and pāmpum tuḷḷal are thriving.